Exploring Optically Fueled Dissipative Self-Assembly of a Redox-Active Perylene Diimide Scaffold - Chatterjee, Oendrila; Pramanik, Anup; Koner, Apurba Lal (Organic Materials, 2022)
Dissipative self-assembly is ubiquitous in nature and underlies many complex structures and functions in natural systems. These processes are primarily enabled by the consumption of chemical fuels. However, dissipative self-assembly processes fueled by light have also been parallelly developed, known as optically fueled dissipative self-assembly. Photoswitchable molecules have been widely investigated as prototypical molecular systems for light-driven dissipative self-assembly. Elucidation of optically fueled dissipative self-assembly by a photo-responsive yet non-photoswitchable moiety however remains elusive. This contribution thus demonstrates the first ever report of an optically fueled dissipative self-assembly arising from a redox active perylene diimide scaffold (DIPFPDI). Photo-reduction of neutral DIPFPDI in a poor solvent such as DMF affords its radical anion and repeated irradiation leads to an increased concentration of radical anion, inducing the construction of an H-type aggregate. Nevertheless, dissolved molecular oxygen can efficiently deactivate the radical anions to their neutral precursors and thus the self-assembled state is no longer sustained. The signature of H-type aggregation is deduced from steady-state UV-Vis, fluorescence as well as time-resolved fluorescence spectroscopy. Theoretical insights reveal that dimerization is more feasible in the charged states because of greater delocalization of the excess charge in the charged states. We believe that these findings will infuse new energy into the field of optically fueled dissipative self-assembly of redox-active chromophores.
Keywords: radical anions; aggregation; perylene; non-covalent forces; fuel-driven